Menschliche Fehler in der Fehlerbaumanalyse - Paweł Buczek (Signal + Draht, 2015)
The family of CENELEC standards envisages a close cooperation between the operator and the manufacturer of a signalling system. An analysis of operational scenarios and related hazards is necessary to determine the safety requirements to be met by thetechnical system. A fault tree analysis is usually established to determine the hazard rate associated with each of the safety functions. Its highest admissible value is called the tolerable hazard rate. It is stipulated by the operator as an input for the manufacturerand constitutes their typical interface. It must therefore be unambiguously and precisely defined.
Keywords: CENELEC; fault-tree analysis; functional safety